System of Weights in Analysis of Inflation - Łyko, Janusz (Układy wag w analizie inflacji, 2009)
Indexes are an instrument of choice for analyzing changes of many economic quantities. Some of them, such as stock market indexes or indexes employed for inflation measurement, may take on fairly complex forms. Index value depends on two coefficients: price and quantity. Quantity, in a sense, is a system of weights used to describe the price vector. This paper addresses the problem of changes in the system of weights for the purpose of calculating consumer price index.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 81, s. 58-70
Keywords: price; inflation; index; weights system